Impact of aggressive management and palliative care on cancer costs in the final month of life. Issue 18 (29th May 2015) - Cheung, Matthew C.; Earle, Craig C.; Rangrej, Jagadish; Ho, Thi H.; Liu, Ning; Barbera, Lisa; Saskin, Refik; Porter, Joan; Seung, Soo Jin; Mittmann, Nicole
<x xml:space="preserve">Abstract</x> BACKGROUND A significant share of the cost of cancer care is concentrated in the end‐of‐life period. Although quality measures of aggressive treatment may guide optimal care during this timeframe, little is known about whether these metrics affect costs of care. METHODS This study used population data to identify a cohort of patients who died of cancer in Ontario, Canada (2005‐2009). Individuals were categorized as having received or having not received aggressive end‐of‐life care according to quality measures related to acute institutional care or chemotherapy administration in the end‐of‐life period. Costs (2009 Canadian dollars) were collected over the last month of life through the linkage of health system administrative databases. Multivariate quantile regression was used to identify predictors of increased costs. RESULTS Among 107, 253 patients, the mean per‐patient cost over the final month was 18, 131 for patients receiving aggressive care and 12, 678 for patients receiving nonaggressive care (P < .0001). Patients who received chemotherapy in the last 2 weeks of life also sustained higher costs than those who did not (P < .0001). For individuals receiving end‐of‐life care in the highest cost quintile, early and repeated palliative care consultation was associated with reduced mean per‐patient costs. In a multivariate analysis, chemotherapy in the 2 weeks of life remained predictive of increased costs (median increase, 536; P < .0001), whereas access to palliation remained predictive for lower costs (median decrease, 418; P < .0001). CONCLUSIONS Cancer patients who receive aggressive end‐of‐life care incur 43% higher costs than those managed nonaggressively. Palliative consultation may partially offset these costs and offer resultant savings. Cancer 2015;121:3307–3315. © 2015 American Cancer Society.